PENGARUH PERTUMBUHAN EKONOMI, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA MODAL DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA PERIODE 2011-2016 - Sri Ayem; Dessy Dyah Pratama (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to determine (1) Influence of Economic Growth on capital expenditure in Special Province of Yogyakarta (2) Influence of General Allocation Fund to Capital Expenditure (3) Influence of Special Allocation Fund to Capital Expenditure (4) Influence of Local Original Income to Capital Expenditure (5)Â Influence of economic growth, general allocation funds, special allocation funds, and local revenues simultaneously to capital expenditures.This type of research is quantitative research. Data analysis technique use multiple regression test which preceded descriptive statistic, classical assumption test, that is normality test, autikorelasi test, multicollinearity test, and heteroscedasticity test. (1) Result of research indicate that: Economic growth have positive effect not significant to capital expenditure with price t count 2,489 <t table 1,6973 with significant level bigger than (p) = 0,05 that is 0,02 (2) Dana Alokasi The general effect is not significantly to Capital Expenditure with the price t arithmetic 0,146> t table 1.6973 and significant value smaller than 0,05 that is 0,885. (3) Special Allocation Fund has effect not significantly to capital expenditure with price t count 1,671> t table 1.6973 and the value is greater than 0.05 ie 0.508. (4) Local Revenue has positive effect not significantly to capital expenditure t count (PAD) 0,749 <t table 1,6973 and significant value less than 0,05 that is 0,461. (5) economic growth, general allocation funds, special allocation funds, and local revenues simultaneously have a positive and significant impact on modi fi c expenditures with a significance value of <0,05.Â Keywords: economic growth, general allocation fund, special allocation fund, local revenue, capital expenditure.Â